Mortality in adolescents and young adults with chronic diseases during 16 years: a study in a Latin American tertiary hospital - Gabriel F. Ramos; Vanessa P. Ribeiro; Mariana P. Mercadante; Maira P. Ribeiro; Artur F. Delgado; Sylvia C.L. Farhat; Marta M. Leal; Heloisa H. Marques; Vicente Odone‐Filho; Uenis Tannuri; Werther B. Carvalho; Sandra J. Grisi; et al. (Jornal de Pediatria (Versão em Português), 2019)
Objectives: To evaluate mortality in adolescents and young adult patients with chronic diseases followed in a Latin American tertiary hospital. Methods: A cross‐sectional retrospective study was performed in a tertiary/academic hospital in the state of São Paulo, Brazil. Death occurred in 529/2850 (18.5%) adolescents and young adult patients with chronic diseases, and 25/529 (4.7%) were excluded due to incomplete medical charts. Therefore, 504 deaths were evaluated. Results: Deaths occurred in 316/504 (63%) of early adolescent patients and in 188/504 (37%) of late adolescent/young adult patients. Further comparisons between early adolescents (n = 316) and late adolescent/young adult patients (n = 188) with pediatric chronic diseases at the last hospitalization showed that the median disease duration (22.0 [0–173] vs. 43.0 [0–227] months, p < 0.001) was significantly lower in early adolescents vs. late adolescent/young adult patients. The median number of previous hospitalizations was significantly lower in the former group (4.0 [1–45] vs. 6.0 [1–52], p < 0.001), whereas the last hospitalization in intensive care unit was significantly higher (60% vs. 47%, p = 0.003). Regarding supportive measures, palliative care was significantly lower in the younger group compared to the older group (33% vs. 43%, p = 0.02). The frequencies of renal replacement therapy (22% vs. 13%, p = 0.02), vasoactive agents (65% vs. 54%, p = 0.01), and transfusion of blood products (75% vs. 66%, p = 0.03) were significantly higher in the younger group. The five most important etiologies of pediatric chronic diseases were: neoplasias (54.2%), hepatic diseases/transplantation (10%), human immunodeficiency virus (5.9%), and childhood‐onset systemic lupus erythematosus and juvenile idiopathic arthritis (4.9%). Autopsy was performed in 58/504 (11%), and discordance between clinical and postmortem diagnoses was evidenced in 24/58 (41.3%). Conclusions: Almost 20% of deaths occurred in adolescents and young adults with distinct supportive care and severe disease patterns. Discordance between clinical diagnosis and autopsy was frequently observed. Resumo: Objetivos: Avaliar a mortalidade entre adolescentes e pacientes adultos jovens com doenças crônicas acompanhados em um hospital terciário na América Latina. Métodos: Foi feito um estudo retrospectivo transversal em um hospital terciário/universitário no Estado de São Paulo, Brasil. Houve mortalidade de 529/2.850(18,5%) pacientes adolescentes e adultos jovens com doenças crônicas, porém 25/529(4,7%) foram excluídos devido a prontuários médicos incompletos. Portanto, foram avaliados 504 óbitos. Resultados: Ocorrem 316/504(63%) óbitos entre pacientes no início da adolescência e 188/504(37%) pacientes no fim da adolescência/adultos jovens. As comparações adicionais entre os pacientes no início da adolescência (n = 316) e no fim da adolescência/pacientes jovens (n = 188) com doenças crônicas pediátricas na última internação mostraram que a duração média da doença [22,0 (0‐173) em comparação com 43,0 (0‐227) meses, p < 0,001], foi significativamente menor nos pacientes no início da adolescência em comparação com os pacientes no fim da adolescência/adultos jovens. O número médio de internação anterior foi significativamente menor no primeiro grupo [4,0 (1‐45) em comparação com 6,0 (1‐52), p < 0,001], ao passo que a última internação na unidade de terapia intensiva foi significativamente maior (60% em comparação com 47%, p = 0,003). Com relação a medidas de suporte, o cuidado paliativo foi significativamente menor no grupo de pacientes no início da adolescência em comparação com o grupo de pacientes no fim da adolescência (33% em comparação com 43%, p = 0,02). As frequências de terapia de substituição renal (22% em comparação com 13%, p = 0,02), agentes vasoativos (65% em comparação com 54%, p = 0,01) e transfusão de hemoderivados (75% em comparação com 66%, p = 0,03) foram significativamente maiores no primeiro grupo. As cinco etiologias mais importantes de doenças crônicas pediátricas foram: neoplasias (54,2%), doenças hepáticas/transplante (10%), vírus da imunodeficiência humana (5,9%), lúpus eritematoso sistêmico de início na infância e artrite idiopática juvenil (4,9%). Foi feita autópsia em 58/504 (11%) e a discordância entre os diagnósticos clínico e pós‐morte foi comprovada em 24/58 (41,3%). Conclusões: Quase 20% dos óbitos ocorreram em adolescentes e adultos jovens com diferentes padrões de cuidados de suporte e doenças graves. A discordância entre o diagnóstico clínico e a necropsia foi frequentemente observada. Keywords: Adolescent, Chronic diseases, Mortality, Hospitalization, Necropsy, Autopsy, Palavras‐chave: Adolescente, Doenças crônicas, Mortalidade, Internação, Necropsia, Autópsia